Empirical evaluation of augmented prototyping effectiveness - Tomáš Koubek; David Procházka (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2012)
Augmented reality is a scientific field well known for more than twenty years. Although there is a huge number of projects that present promising results, the real usage of augmented reality applications for fulfilling common tasks is almost negligible. We believe that one of the principal reasons is insufficient usability of these applications. The situation is analogous to the desktop, mobile or cloud application development or even to the web pages design. The first phase of a technology adoption is the exploration of its potential. As soon as the technical problems are overcome and the technology is widely accepted, the usability is a principal issue. The usability is utmost important also from the business point of view. The cost of augmented reality implementation into the production process is substantial, therefore, the usability that is directly responsible for the implemented solution effectiveness must be appropriately tested. Consequently, the benefit of the implemented solution can be measured.This article briefly outlines common techniques used for usability evaluation. Discussed techniques were designed especially for evaluation of desktop applications, mobile solutions and web pages. In spite of this drawback, their application on augmented reality products is usually possible. Further, a review of existing augmented reality project evaluations is presented.Based on this review, a usability evaluation method for our augmented prototyping application is proposed. This method must overcome the fact that the design is a creative process. Therefore, it is not possible to take into account common criteria such as time consumption.